Os usos e as traduções da educação ambiental na produção do cotidiano escolar - Vieiras, Rosinei Ronconi (2012)
The paper discusses the relation culture-nature from one perspective of fragmentation carried out during modernity, through the Cartesian thought. It approaches the relevance of a complex thought for an environmental education, in which it is acknowledged the importance of us seeing ourselves as part of the nature, participants and inter dependent on it. It focuses on the environmental education produced/weaved and translated into the school daily life. The research presents, as one of the main goals, the problematization of different uses of the environmental education carried out by the individual’s practitioner of the school daily life, as well as the translation presented by the people who are part of such daily life. It is methodologically involved with the purpose of/in/with the daily and assumptions of the cartography, searching for follow-up and understanding the narratives and everyday practices present in two public schools in the district of Colatina, State of Espírito Santo. When following the process, there is an intervention and with it, the research aims at discussing the environmental practices present in all the schools’ daily life. Based on the idea that every research is also a political bet, that one is engaged in the acknowledgement that, among the complexity of the school daily life, environmental practices are present and they can be potentiated and potentiate new means to be present and be part of the world. Therefore, it considers, that many daily environmental practices occur in contexts not always visible to the eyes of a univocal rationality and that, although some may be considered reductionist, it is notable an environmental practice in movement, being weaved in the everyday school life. Such movement is trailed to those daily practices that, if potentiated, may significantly contribute for the predominance of more ethical relations and committed with the environment, mining the culture-nature dichotomist paradigm.